Vaginal microflora in the preand post-operative of ginecologic surgeries - Silvino, Marina CM; Giraldo, Paulo César; Vicentini, Regina Maria R; Eleutério Júnior, José (Brazilian Journal of Sexually Transmitted Diseases, 2006)
Introduction: many are the components and aspects that can vary in the composition of the vaginal content. Objective: to determine if there’s variation in thevaginal microflora between the pre and post-operative in patients submitted to gynecologic surgeries in an university‘s hospital. Methods: the vaginalmicroflora of 41 women undergoing gynecologic surgeries was evaluated. Vaginal smears were collected in pre-operative (day of internation) and post-operative (day of discharge), were submitted to Gram stain and evaluated by microscopy. The vaginal microflora was characterized according to the presenceof Lactobacillus spp in type I (>80%), II (between 5% and 80%) and III (<5%). For the statistical analysis, Fisher exact test and McNemar test were used.Results: among 41 cases studied, 21 were abdominal and the other 20, vaginal. Normal vaginal microflora (type I) was obtained in just 34,1% of the cases. TypeIII microflora was obtained in other 34,1% of the cases. After the surgical act, these numbers went to 7,3% of type I and 73,2% of type III (p<0,05). In relation tothe surgical access, there was a reduction in the amount of Lactobacillus from 17,1% to 7,3% in the abdominal surgeries and from 17,1% to zero in the vaginalones, without a significant statistical correlation between the type of microflora obtained and the type of surgical access. Conclusion: there was a significantchange in the vaginal microflora in the early post-operative of gynecologic surgeries, despite the use of profilatic antibiotics, but independently of the surgicalaccess. Perhaps the use of profilatic antibiotics could be reduced if the patients that carry abnormal vaginal microflora were treated before surgery.